Enhanced wireless end-to-end IoT hydroponic system - Ali, Nur Alisa; Hashim, Nik Mohd Zarifie; Mohamad, Najmiah Radiah; Ja'afar, Abd Shukur (Human Resource Management Academic Research Society, 2024)
In uncontrolled environments, the effects of global warming present significant challenges to effective plant cultivation. Recent technological advancements have bridged the gap between agricultural practices and IoT technologies, highlighting the importance of precise fertilizer management to optimize production costs. Thisstudy proposes an IoT-based system designed for hydroponic agriculture that monitors and regulates fertilizer application. Utilizing ESP32 devices, one endpoint collects data from sensors measuring pH, humidity, and temperature. A master node aggregates this data, displays it on an LCD, establishes a local Wi-Fi connection, and transmits the information to the Cayenne IoT platform for comprehensive monitoring. The system continuously monitors pH levels via a nodeMCU, activating a pump through a relay to dispense precise amounts of fertilizer as needed. This automated system enables convenient data access through the Cayenne dashboard and significantly reduces excessive fertilizer use, proving especially effective in regions with limited Wi-Fi connectivity.